Treinamento por meio dos pacotes formativos X problematização e reflexão da formação continuada docente na educação básica - Velho, Priscila de Campos (2024)
The general objective of this dissertation was to discuss the paths of training continued, comparing the idea of ​​training through training packages with the proposal of a process that is capable of problematizing and reflecting on training teacher in basic education. The research had the following specific objectives: conceptualize and characterize the types of continuing education, verifying their relevance in terms of practice pedagogical in the school environment; understand the guidelines in official regulations regarding continuing teacher training, as well as recontextualizing training packages; to analyze critically the training packages of the Ayrton Senna Institute based on academic literature and legal regulations studied in this dissertation. The research problem was guided by following question: do training packages based on training provide training continue to be truly qualified to do teaching? The theoretical framework adopted was anchored in the contributions of authors Bersntein (1996), Benincá (2002; 2010), Charlot (2020), Dewey (1971), Freire (2002; 2011), Nóvoa (1992; 2019), Nussbaum (2010), Santos (2008) and Tardif (2002). Documentary research focused on analyzing current legislation and public educational policies. Theoretical/bibliographical research provided a basis theoretical, exploring the concept of continuous training through the contributions of authors who served as the basis for defining the analysis categories. Proposals for training of the Ayrton Senna Institute to analyze the extent to which they comply with the legal requirements and the training format adopted, allowing a critical look that align with the objective of this research. In addition to the introduction, the dissertation, in the second chapter, seeks to conceptualize the training proposals that are currently verified in teaching practice; the third chapter is based on continued training within the regulations official, such as the 1988 Constitution, the Education Guidelines and Bases Law (LDB 9394/96), the National Curricular Guidelines for Basic Education (DCNs, 2001), the National Education (PNE, 2014) 1 and 2, the National Common Curricular Base (BNCC, 2017), BNCFormação (2019) and the National Curricular Guidelines for Continuing Training of Teachers for Basic Education - BNC-Continuing Training (2020); the fourth chapter critically analyzes the training packages developed by the Ayrton Senna Institute. As general conclusion, it is possible to state that the continued training of teachers in Brazil faces significant structural and cultural challenges. The Ayrton Senna Institute (IAS) offers packages training courses that often prioritize quick and technical solutions, neglecting a deeper reflection on teaching practice. In this sense, this research questions whether these packages really qualify teachers effectively. The analysis reveals that the IAS programs tend to standardize and measure results, disregarding the complexity and the integrality of the educational process. For this reason, it is essential to have a more contextualized and democratic process that values ​​the active participation of teachers and local specificities. Public policies must promote continued training that transcends marketing logic, integrating technical, methodological, socio-emotional, ethical and cultural aspects to face the challenges of the school environment contemporary.